Injuries in taekwondo athletes - Oliveira, F. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: Taekwondo is an Olympic sport with direct contact of high-impact between the competitors and its movements combine complexity, strength and high speed. These characteristics place demands on body structures and may subject the athletes to injury. The athletes are often required to give maximum physical and mental effort to obtain good results further increasing the risk of injury. The objective of this paper is to evaluate the incidence of injuries in high level taekwondo competitors. Methods 43 taekwondo black-belt athletes (31 male and 12 females), with a mean age of 20.8 ± 3.2 years old (male: 21.5 ± 3.1 years old; female: 19.1 ± 2.8 years old) participated in the study. Information related to practice-time, competitive level, injury occurrence and others factors was collected. Results Average number of injuries was 5.81 ± 3.54 and 4.08 ± 2.07 for male and female athletes respectively. The most affected regions were feet (16.2%), followed by knee and ankle (12.2%) and the majority of injuries (55.8%) occurred during competition. The majority injuries were classified as level I degree sprains (46.3%) and with the lower extremity accounting for 54.1% of injuries, the most frequent types of injury being foot contusions (21.0%), followed by ankle sprains (10.9%) and lower back pain (9.6%). Conclusions It was concluded that the high injuries index in taekwondo is related to the intensity of training and participation in competitions. There was also a lack of awareness and knowledge of injury among the taekwondo competitors. There is a need for a prevention program and safety measures associated with the special risks and needs of taekwondo athletes.